Novel approach for detection of foreign particles in beverages - Forstner, Judith; Benning, Rainer; Procelewska, Joanna; Osorio Nesme, Anuhar; Mauermann, Marc; Hanke, Tilo; Majschak, Jens-Peter; Delgado, Antonio (BrewingScience, 2012)
Foreign particles in food and beverages constitute a serious problem to industry, due to company image and legal responsibility, and the consumer, whose health might be threatened. In this case random testing does not suffice and every container has to be individually tested for absence of such particles. Consequently, there is an urgent need for a reliable, fast and low cost system, which can be automated and which can be applied to filled and closed containers. The presented paper describes a system, which is based on rotatory movement of bottles. Due to their importance glass and PET bottles were used as examples for the approach, forcing particles like glass splinters to move to the wall. Multiple contacts of the particle upon the wall follow from this proceeding and are recorded by a piezo sensor. After processing the resulting signals allow the detection of glass particles with dimensions down to 1 mm x 1 mm x 1 mm in aqueous liquids, like water, beer, butter milk or orange juice. Besides the costs an advantage of the system lies in the characteristic that an optical access is not necessary, both with respect to the material of the bottle and the contained liquid.
UnivIS-Import:2015-04-14:Pub.2012.tech.ITC.stmmec.novela
Keywords: Bverages; Detection system; Food; Foreign particles; Multi contact; Piezo sensor